Pendekatan Interdisipliner dalam Studi Islam: Metodologi dan Implikasinya di Indonesia - Ayu, Diyan Putri; Nurrohman, Dede (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Correct understanding reveals the true path of faith and belief in the true teachings of Islam. An incomplete perception arises when the Islamic approach is less comprehensive, giving rise to various situations. This approach is used to generate a complete and complete understanding of Islam in order to help Muslims face and answer various difficulties related to Islamic teachings. Efforts to study religion, especially Islam, are not only carried out by Muslims, but also by people outside the Muslim community. Islamic studies carried out among Muslims are of course very different in purpose and motivation from those carried out by those outside the Muslim community. This research takes the form of qualitative research, this method is very suitable for understanding social phenomena, problems or symptoms in humans by collecting as many in-depth facts as possible, the data is presented in verbal form, not in numerical form. This research produces conclusions. An interdisciplinary approach is one that uses an integrated evaluation of several related scientific views to solve problems. An interdisciplinary approach is a study that uses various methodologies or views. In research, for example, using philosophical, sociological, historical and normative perspectives at the same time.